TEORI SASTRA MARXIS DAN APLIKASINYA PADA PENELITIAN KARYA SASTRA ARAB MODERN - Fadlil Munawwar Manshur (Fakultas Sastra Universitas Negeri Malang, 2012)
Many works of the modern Arabic literary contain the class struggle themes, especially the struggle of the oppressed versus the oppressors. Indeed, the theme of class struggle in the works of Arabic literary is moral and social mirror of Arab society itself. By reviewing the works of Arabic literature from the perspectiveof Marxist literary theory in mind that the works of modern Arabic literature is the representation of violent social class conflict within the Arab society, so the use of this theory can further the work of Arabic literature presents a more meaningful, authentic, and can avoid the marginalization of the Arab literary works of construction of cultural and ideological society.